2014
DOI: 10.1371/journal.ppat.1003994
|View full text |Cite
|
Sign up to set email alerts
|

Post-Translational Regulation via Clp Protease Is Critical for Survival of Mycobacterium tuberculosis

Abstract: Unlike most bacterial species, Mycobacterium tuberculosis depends on the Clp proteolysis system for survival even in in vitro conditions. We hypothesized that Clp is required for the physiologic turnover of mycobacterial proteins whose accumulation is deleterious to bacterial growth and survival. To identify cellular substrates, we employed quantitative proteomics and transcriptomics to identify the set of proteins that accumulated upon the loss of functional Clp protease. Among the set of potential Clp substr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
98
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 77 publications
(103 citation statements)
references
References 33 publications
5
98
0
Order By: Relevance
“…Thus far, RpsL has been identified as a Clp protease target under normal culturing conditions (27). Upon expression profile analysis, we found no expression of rpsL within Mtb at early stages or reaeration, whereas there was increased expression of rpsL at later stages of reaeration within the mutant (Fig.…”
Section: ͼ2-fold Were Induced Within Mtbmentioning
confidence: 67%
See 3 more Smart Citations
“…Thus far, RpsL has been identified as a Clp protease target under normal culturing conditions (27). Upon expression profile analysis, we found no expression of rpsL within Mtb at early stages or reaeration, whereas there was increased expression of rpsL at later stages of reaeration within the mutant (Fig.…”
Section: ͼ2-fold Were Induced Within Mtbmentioning
confidence: 67%
“…Interestingly, B , rpsL, dnaK, and Rv3334 have been identified as Clp protease substrates (27). As such, upon day 1 of hypoxia, these genes were induced in Mtb but were not induced at later time points (Fig.…”
Section: Volume 290 • Number 4 • January 23 2015mentioning
confidence: 86%
See 2 more Smart Citations
“…Raju et al identified 132 and 107 putative ClpP substrates in M. tuberculosis and Mycobacterium smegmatis, respectively, by quantitative proteomic profiling of the wild-type and ClpP knockdown strains (40). The two ClpP homologs (ClpP1 and ClpP2) in M. tuberculosis and M. smegmatis form the ClpP proteolytic core and are essential for mycobacterial survival in vitro and during infection of mice (33,40,41).…”
mentioning
confidence: 99%